Detergents - useful or dangerous. Discussion of the toxic effects of detergents based on studies - Rafał Tkaczyk; Michał Tchórz; Gabriela Świątek; Weronika Sosnowska; Aleksandra Brzozowska; Maria Tomkiewicz; Jakub Tomczyk; Maciej Tomkiewicz; Kornelia Trusz; Iwona Wanat (Kazimierz Wielki University, 2023)
Introduction and purpose: Detergents are compounds that constitute the main component of cleaning products. Due to their varied chemical structure, they have different functions and a wide range of applications. The aim of this study is to draw attention to the problem of toxic effects of detergents on the basis of analysis of cases of detergent poisoning by patients of the Toxicology and Cardiology Ward of the Stefan Cardinal Wyszyński Provincial Hospital in Lublin. Material and methods: The study was retrospective in nature. It used an analysis of the medical records of 11707 intoxications in patients between 01.01.2013 and 31.12.2022, from which a group of individuals with a diagnosis of T55 according to the ICD 10 classification "Toxic effects of soaps and detergents" consisting of 36 cases was selected. Results: The study population consisted of 18 (50%) women and 18 (50%) men. The majority- 19 patients (52.78%) were exposed to the toxic effects of detergents accidentally. 10 patients (27.78%) were suicide attempts. Accompanying medical conditions were mostly psychiatric disorders, with alcohol dependence syndrome predominating - 9 cases (25%). The majority - 33 patients (91.67%) intoxified themselves with detergents in the form of liquids and solids by the oral route . Conclusions: Despite their usefulness in households and industry, detergents contribute to adverse health effects in situations of accidental exposure or intentional intake. In order to reduce the number of complications, preventive measures should be implemented - such as storing detergents in less accessible areas, in original boxes with retained labels, and increasing funding for psychological-psychiatric care in a crisis situation.